PENGARUH UKURAN BANK, BOPO, RISIKO KREDIT, KINERJA KREDIT, DAN KEKUATAN PASAR TERHADAP NET INTEREST MARGIN (Studi Perbandingan pada Bank Persero dan Bank Asing Periode Tahun 2008-2012) - NIHAYATI, AINI; WAHYUDI, SUGENG; SYAICHU, MUHAMMAD (JURNAL BISNIS STRATEGI, 2014)
AbstractThis research intends to analyze the influence of Bank Size, Operational Cost of Operational Income (or BOPO), Credit Risk, Credit Performance and Market Power on the Net Interest Margin (NIM). It examines arrange of data set from Persero and Foreign Banks between2008-2012. As such, the goal of this research is to determine whether there arecomparative differences in the influence of Bank Size, BOPO, Credit Risk, CreditPerformance and Market Power on the NIM of Persero and Foreign Banks.The researcher utilizes purposive sampling method with four Persero Banks and four Foreign  Bank from period 2008-2012. This research used multiple regression analysis, Classical Test  Assumptions and Goodness of Fit Test. A Chow test is carried out to find out whether there  are comparative differences in the effects of Bank Size, BOPO, Credit Risk, Credit  Performance and Market Power on the NIM of Persero and Foreign Banks.Findings from this research conclude that Bank Size does not have significant effect on the NIM of sampled Persero and Foreign Banks. In Persero Banks, BOPO has negative effect on NIM; Credit Risk, Credit Performance and Market Power has positive effect on NIM. Meanwhile, in Foreign Banks, BOPO and Credit Performance has negative effect on NIM; Credit Risk and Market Power has positive effect on NIM. Based on the Chow Test result, it can be inferred that, there are comparative differences in the influence of Bank Size, BOPO, Credit Risk, Credit Performance and Market Power on the NIM of Persero and Foreign Banks.